Anodal Transcranial Direct Current Stimulation Reduces Competitive Anxiety and Modulates Heart Rate Variability in an eSports Player - Machado, Sergio (2022)
Previous research has recently shown that high cognitive and somatic anxiety and low self-confidence, before and during sport competitions have a significant correlation with heart rate variability (HRV) changes and can reduce overall athletic performance. Therefore, interventions, such as transcranial direct current stimulation (tDCS), can be a potential tool to reduce psychophysiological anxiety-related and enhance athletic performance. We present a case of a male professional athlete of eSports. We explored the effects of a single session of anodal tDCS (a-tDCS) at 2mA over the dosrsolateral prefrontal cortex (DLPFC) on competitive anxiety and HRV assessed in baseline (BL), pre-tDCS, post-tDCS and postgame moments and compared between moments. Here, we found a decrease in somatic and cognitive anxiety, as well as an increase in self-confidence and in SDNN index in the post-tDCS moment compared with BL, pre-tDCS and post-game moments. These findings can be a result of an acute change in the attentional state, influencing the processing of threatening information essential for cognitive anxiety and of a self-regulatory process, which can regulate physiological arousal response, such as HRV.